Pegada hídrica da cultura do feijão de inverno irrigado para o Médio Norte do Estado de Mato Grosso - Silva, Célio Jacinto da (2024)
The Brazilian agricultural sector is a very significant segment in terms of the use of water resources, mainly in the State of Mato Grosso, which is home to one of the largest irrigation centers in the country, in regions characterized by the Amazon biome. Since water resources are finite and their use is intensive, quantifying water use in agriculture can contribute to the adoption of public policies for water resource management. In this sense, the objective of this work was to calculate and evaluate the Water Footprint of irrigated winter beans in the Middle North of the state of Mato Grosso in the years 2021 to 2023. Using the CROPWAT software, it was possible to calculate the evapotranspirometric demand of the bean crop in region and carry out an irrigation balance. The green and blue Water Footprints were obtained using crop evapotranspiration to calculate water demand, with an average of 2,381.0 m³.ha⁻¹, while the gray Water Footprint was calculated using nitrogen fertilizer application rate parameters to crops, which was 100 kg. ha⁻¹, and its leaching into the soil, with an average of (342.44 m³.t⁻¹), highlighting the importance of adequate control of fertilizer application. In the study area, the Dama Carioca TAA S2 variety was cultivated, presenting a good average productivity of 2,921.0 kg. ha⁻¹, surpassing the national and regional averages. The average Total Water Footprint of beans was 1,157.96 m³.t⁻¹, with 70.43% attributed to the Blue Water Footprint(815.52 m³.t⁻¹) and 29.57% attributed to the Gray Water Footprint (342.44 m³.t⁻¹). The absence of Green Water Footprint (0%) reflects the practice of planting during the dry period. Compared to previous studies, the results indicate that bean production in the studied region has an excellent Water Footprint index. These results have valuable implications for sustainable agriculture, emphasizing the importance of conscious management of water resources to improve agricultural production, since the Water Footprint indicator contributes to discussions of crop planting potential in certain regions.